FORMULATION OF SPECTRUM FEE TO ENCOURAGE THE FREQUENCY SPECTRUM UTILITY EFICIENCY CASE STUDY : GSM AND FWA SERVICES IN INDONESIA - , ISMAIL
Radio frequency spectrum as a limited and high value natural resource, especially for cellular frequency band should be managed and used effectively and efficiently. Government as the national frequency spectrum managers and providers of mobile communications that use the frequency spectrum are always required to further enhance the efficiency of spectrum utilization. Based on the recommendation ITU-R SM 1046-2 about spectrum efficiency, that efficient spectrum utilization is defined as a capability of delivering the maximum information with a certain bandwidth, in certain areas and certain times. The important instrument in promoting the achievement of the frequency spectrum utilization efficiency is the imposition of Frequency fee (Called “BHP-F”) to the user frequency. In the case of Indonesia, particularly in the frequency band GSM (Global System for Mobile Communication) and FWA (Fixed Wireless Access), which provides mobile communication services, BHP-F formula imposed has many weaknesses, including not promote the efficiency of spectrum utilization, so needs a change. Changes in these formulations need to be done carefully to avoid the risk of government revenues and operating costs of mobile communications provider that can interfere with the overall service. BHP-F Formula Alternatives recommended by the ITU through the recommendation ITU-R SM 2012-2 may be considered as proven capable of encouraging increased efficiency of spectrum utilization in various countries. But for Indonesia's situation needs to be done by adding a modification to the principle of incentive factors Administrative Incentive Price (AIP), which can encourage the utilization of spectrum in the territory of Indonesia which low-income economies. Based on the combination of the recommendation ITU-R SM 2012-2 and the AIP principles could be proposed a new BHP-F formula. To specify an alternative choice of the best BHP-F must be calculated and analyzed quantitatively in order to ensure that the efficiency of spectrum utility increases but economically feasible for providers of mobile communications and government revenue is maintained. For that prepared a techno-economic model of telecommunications in accordance with the conditions of telecommunication carriers, geographic and economic factors in Indonesia. The model is used to perform calculations and analysis of three types BHP Alternative namely BHP Existing (BHP-FISR), BHP based on the bandwidth (BHP-FPITA) and BHP-FUSULAN which is the result of modification of the formula recommendation ITU-R SM 2012 - 2 adapted to Indonesian conditions. From the calculation and analysis using a model of techno-economic telecommunication who built proved that the BHP-FUSULAN could encourage the increased frequency spectrum utility efficiency better and give justice to the providers of mobile communications. BHP-FUSULAN proven to have a utility value of the highest frequency, the IRR of 35-40%, BHP-FUSULAN able to provide utilities in the year 2020 reached 92 382 million kHz.km2, while BHP-FISR only reached 92 109 million kHz.km2. While in the IRR is 40% -45%, BHP-FUSULAN only capable of having a high utility. In addition, although all three formulations of BHP-F was able to push the utility increase of almost 10-fold, from 9802 million to 92 805 million kHz.km2 during the period of ten years, but the burden of payment for BHPISR will go up sharply, while with BHP-FUSULAN and BHP-FPITA will be more stable, which means the potential of financing would be less risky and more likely to increase the utility Frequency Spectrum. The model can also be used to conduct simulations of various options, such as changes in the frequency band and the reduction or additional bandwidth in the particular case of return and bandwidth reduction will provide economic viability (IRR> 10%) is only valid when used BHP-FUSULAN or BHP-FPITA and this case will not be obtained when used BHP-FISR. Models are arranged in addition has several advantages that can display the results in a quantitative and flexible enough but also has some limitations that some model parameters such as tariffs and ARPU is quite volatile, so the parameters need to analyze the sensitivity and periodic adjustment. In addition further research must be done by testing the model against other frequency bands and trials of other Government policies are similar to the accuracy of the results of the more believed to be a model.